ANIMATION AND CULTURAL RESISTANCE IN IRAN: A THEMATIC ANALYSIS OF PERSEPOLIS, WINDOW HORSES, AND TEHRAN TABOO - Matin, Alireza Azeri (Sanata Dharma University, 2025)
Animation has long served as a powerful medium for cultural resistance, providing a platform for marginalized voices to challenge dominant narratives, critique oppressive systems, and express identity. However, despite a growing body of scholarship on cultural resistance in authoritarian contexts, few studies have investigated full-length animated films produced by or about Iranians as sites of ideological contestation. This article maps how animation, particularly works created in exile, functions as a potent medium of cultural resistance that subverts state censorship and challenges dominant narratives in the Islamic Republic of Iran. Drawing on qualitative visual and narrative data from Persepolis (2007), Window Horses (2016), and Tehran Taboo (2017), the study interprets these films through a framework of critical discourse and ideological analysis. Rather than merely documenting repression, the films collectively reveal how cultural resistance is enacted through female agency, poetic expression, and everyday defiance embedded in urban and diasporic spaces. These acts of dissent are often subtle yet deeply political, highlighting the resilience of Iranian identity in the face of surveillance, displacement, and moral control. Ultimately, the study underscores the strategic role of animation in circulating marginalized voices across national borders, offering valuable insights into the dynamics of resistance in tightly controlled media environments.